Blackstone's Statutes on Employment Law 2021-2022 - Richard Kidner (United Kingdom Oxford University Press, 2021)
Unsurpassed in authority, reliability and accuracy; the 2021-2022 edition has been fully revised and updated to incorporate all relevant legislation for employment law courses. Blackstone's Statutes on Employment Law is an abridged collection of legislation carefully reviewed and selected by Richard Kidner. With unparalleled coverage of employment law, Blackstone's Statutes on Employment Law leads the market: consistently recommended by lecturers and relied on by students for exam and course use. Blackstone's Statutes on Employment Law is: - Trusted: ideal for exam use - Practical: find what you need instantly - Reliable: current, comprehensive coverage - Relevant: content reviewed to match your course.
Keywords: Law; Employment law; (ASB-2400) Law for Business